Planejamento ambiental urbano: A relação entre a cobertura vegetal e temperatura superficial na Cidade de São Carlos, São Paulo, Brasil - Camacho, Vitor Augusto Luizari [UNESP]; Moschini, Luiz Eduardo (Fronteiras: Journal of Social, Technological and Environmental Science, 2021)
The rapid urban expansion of cities has modified the natural landscape in Brazil changing the environmental and climatic conditions, from this the studies involving urban planning, environment and geotechnologies present solutions to current problems of cities, such as floods, heat islands and lack of green spaces. The objective of this work is to analyze the relationship between vegetation cover and surface temperature in the city of São Carlos, São Paulo, Brazil. Images from the Landsat-8 satellite were used, by means of digital image processing and remote sensing techniques. For the surface temperature band 10 (thermal) was used and for the vegetation cover bands 4 (red) and 5 (near infrared) of the Landsat 8 satellite, by means of the NDVI (Normalized Difference Vegetation Index) vegetation index. The work was carried out in the QGIS software. As analysis were determined the correlation coefficients and determination between the indices from control points with both data in the urban perimeter. As a result, it was possible to observe a negative correlation between vegetation cover and surface temperature. Areas with the highest temperatures (37.4°C) were associated with the absence of vegetation, the high degree of construction densification and soil sealing. Studies like this one reinforce the importance of vegetation cover in urban areas for thermal control and well-being of resident populations in the face of the growing effect of climate change affecting urban centers. Proposals and mitigation actions should be part of a set of public policies applied to cities, thinking systemically and dynamically.
Keywords: Heat Island; Landsat 8; Remote sensing; Urban climate